A Systematic Review of Youth-to-Parent Aggression: Conceptualization, Typologies, and Instruments - Ibabe, Izaskun (Frontiers in Psychology, 2020)
Youth-to-parent abuse (YPA) could be defined as a repetitive pattern of abusive behavior toward a parent or the person playing this role by an adolescent child or adult child who is usually still living in the family home. The conceptualization of YPA is currently somewhat flawed, and several instruments have been used in this research context. The objective of this paper is to review the conceptualization of YPA to establish a full definition to present the typologies of YPA depending on the coercion level and nature of the violence, as well as to identify the best assessment instrument through a systematic review of such instruments, using the COSMIN checklist. In this paper, a critical review of the literature on conceptualization and measuring instruments will be performed. The way to diagnose abusive YPA is by using Abusive Behavior by Children-Indices ABC-I. This study demonstrated that it was possible to discriminate the four typologies of YPA (Abusive, Defensive, Affective, and Situational) and the initial psychodiagnosis of a YPA situation would help in the individual or family intervention, as well as prevent more severe situations of YPA by applying early intervention.